Fuzzy encoder framework for four layers color QR code - Badawi, Bakri; Mohd Aris, Teh Noranis; Mustapha, Norwati; Manshor, Noridayu (Faculty of Computer Science and Information Technology, University of Malaya, 2019)
QR code is a popular type of two-dimension barcode due to high demand of QR code which makes it an active research area specifically to overcome QR code limitation. One of QR code limitation is encoding data size limitation. In this paper, we proposed four layers QR code encoder utilizing fuzzy technique to overcome size limitation. The framework extended the maximum capacity for three layers color QR code by 25%. The fuzzy encoder will select the best-fit color QR code in the aspect of the number of colors according to the file size and the space on paper. Then, the encoder will divide the file into a maximum of four layers of a black and white QR code and give each layer a specific color by color multiplexing for those QR codes. We produced a color QR code with a maximum capacity of four times larger than existing black and white QR code. The encoder also proposed color reference on the locator pattern in the QR code to easily identify the number of colors used in the generated color QR code.